Trade effects of export taxes - Olga Solleder (Graduate Institute of International and Development Studies, 2013)
Export taxes usage has recently risen. They are widely presumed to affect trade, but the lack of data has prevented a systematic evaluation of their trade effects. Based on a new dataset of tax rates at the product level, this paper estimates the distortionary trade effects of export taxes. The results, which are based on theory-consistent estimation of a structural gravity model, indicate that the elasticity of trade quantities to tax is -1.8 on average, rising to -5.5 for extractive sectors. The effects are driven by homogeneous goods. The results suggest that the burden of export taxes is shared by exporters and importers and that export taxes play a role in the rise of world prices.
Keywords: F13; F42; O24; Q37; H23; 330; export taxes; export duties; export restrictions; export policy; trade policy; panel gravity models; GATT/WTO; Exportsteuer; Handelseffekt; WTO-Regeln; Panel; Gravitationsmodell; Welt